Pear Juice Clarification Using Polygalacturonase from Beauveria bassiana : Effects on Rheological, Antioxidant and Quality Properties - Ayodeji Emmanuel Amobonye; Prashant Bhagwat; Faith Matiza Ruzengwe; Suren Singh; Santhosh Pillai (Polish Journal of Food and Nutrition Sciences)
Although pear is one of the most preferred fruits globally due to its high nutrient content, its juice products have not received equal consumer acceptability due to their undesirable haziness and turbidity. However, enzymatic treatment of juice has been noted to improve the overall acceptability of juices better than traditional decantation, filtration, and heating methods, which are either expensive or detrimental to the product quality. In this study, pear juice was effectively clarified using partially purified polygalacturonase from an entomopathogenic fungal endophyte Beauveria bassiana SAN01. The optimization of the juice clarification process led to 137% improvement in clarification compared to control, under optimal conditions of 39.37 U/mL enzyme load, 36.87°C temperature and 2.75 h treatment time. Results also showed that the polygalacturonase treatment resulted in a significant decrease in viscosity and an increase in the pseudoplasticity of the pear juice as the rheological data of the juice was observed to fit adequately into the power law model (R 2>0.9). Furthermore, the enzyme-assisted juice clarification was found to reduce browning index (-14.34%) and turbidity (-19.72%) while increasing the reducing sugar content (9.55%). Unlike some conventional juice treatments, the polygalacturonase treatment preserved the antioxidant potential and the total phenolic contents of the pear juice as no significant changes were observed after the treatment. This study thus demonstrates the efficacy of a fungal polygalacturonase in improving pear juice quality as well as the potential applicability of B. bassiana enzymes in the food industry.